NEGARA DAN LEMAHNYA GOVERNABILITY Studi Eksploitasi Pasir Galunggung di Kecamatan Sukaratu Tasikmalaya - Subhan Agung (Fakultas Ilmu Sosial dan Ilmu Politik, 2011)
Weak government control of sand mining business people showed weak governability Galunggung government. The government should be able memoderatori private competition that harm the public interest. Based on the realities on the ground, people are